Developing a Solution for Controlling Technical Systems in Airports Based on Flight Information Display System - Huynh, Thai Hoang (Journal of Technical Education Science, 2025)
The paper presents a solution for automatic control of technical equipment in airports, such as electricity, air conditioning, lighting, and baggage conveyor systems… based on the flight information display system to enhance operational efficiency and cost savings according to specific flight schedules. Firstly, the control solution for technical equipment in airports based on building management software is introduced. Next, the paper proposes a solution to update the scheduling database for equipment control based on flight information display system data. A database is designed with three data tables, of which one data table storing device group information and two data tables storing information about arrival and departure flights. A program is developed to read data in the flight information display system and store data in the database. A middleware is employed to retrieve data from the database and integrate it into the building management software to control device groups in the airport following flight schedules. Simulation results demonstrate that technical equipment can be automatically controlled to align with departure and arrival flight schedules. In case of flight delays or cancellations, the equipment control schedule is automatically updated, facilitating energy savings and operational cost reduction.